Transcriptional regulation in Plasmodium falciparum: characterisation of TBP-like protein - Michowicz, Joanna (Department of Molecular and Cell Biology, 2025)
Malaria persists as a devastating disease resulting in a high burden of morbidity and mortality worldwide. The most severe form of malaria is due to infection with Plasmodium falciparum, accounting for the overwhelming majority of malaria deaths. Despite extensive efforts to curb transmission, recent reports of drug resistance to front-line antimalarial treatments coupled with the continuing lack of effective vaccines implores the production of novel anti-malarials. Both parasite development and pathogenicity are tightly controlled by a highly regulated gene expression program. However, regulation at the level of transcription initiation is hitherto poorly understood. The TATA-binding protein (TBP) is a universal transcription factor required for transcription by RNA polymerase I, II and III. Multiple gene duplication events throughout eukaryotic evolution have resulted in many eukaryotes harbouring more than one TBP family protein. In metazoans, TBP paralogs have been shown to play important roles in cell-specific developmental gene expression programs. However, research into the roles of TBP paralogs in unicellular eukaryotes is extremely limited. Bioinformatic analyses have identified a P. falciparum putative TBP-like protein (PfTLP). Previous research in our laboratory demonstrated that PfTLP has DNA-binding activity and that it harbours two insertions, which are predicted intrinsically disordered regions (IDR1, IDR2), within its structurally conserved TBP DNA-binding domain. In recent years there has been mounting evidence that IDRs mediate liquid-liquid phase separation, a process which has transformed our understanding of cellular organisation and regulation of key cellular processes. The functional relevance of these IDRs is unknown. Therefore, to elucidate their role, this study was divided into three parts: (i) a bioinformatic analysis to investigate the prevalence of disordered regions within Apicomplexan TLPs, (ii) an investigation into the role of these regions in PfTLP DNA binding and (iii) an in-depth characterisation of phase separation by PfTLP IDRs and full-length PfTLP. This study highlights the prevalence of TLPs within Apicomplexa and, moreover, the presence of a conserved IDR2 in diverse Apicomplexan species. Both IDR1 and IDR2 were shown to bind to DNA and analysis of a panel of newly generated PfTLP deletion mutant protein constructs revealed that this DNA-binding activity stabilises PfTLP-DNA complexes. Finally, a systematic characterisation of the phase-separating properties of PfTLP IDRs and full-length PfTLP was carried out, using PfRBP1-CTD and PfTBP-IDR for comparison. It was found that PfTLP-IDR1 readily undergoes liquid-liquid phase separation (LLPS) at low protein concentrations, forming dynamic condensates that homogenously mix with dsDNA. In contrast, PfTLP-IDR2 does not self-assemble in the absence of phase-separating interaction partners. Interestingly, at a physiological protein concentration, full-length PfTLP was found to form clustered assemblies in isolation but formed separate, mixed condensates in the presence of dsDNA, suggesting a role of DNA in the regulation of PfTLP condensate formation. In addition, the interaction of PfTLP with DNA condensates was found to be independent of IDR1 and IDR2, consistent with the DNA-binding activity of the PfTLP structured domain. Thus, this study yields novel insights into the DNA-binding and phase-separating properties of PfTLP that may contribute to the assembly of the RNA polymerase II transcription initiation machinery of this divergent parasite.